Perivulvar squamous cell carcinoma in a cow - ORAL, H.; BEYTUT, E.; KURU, M.; KARAKURT, E.; DEMIR, M. C.; ÖZAYDIN, İ. (Journal of the Hellenic Veterinary Medical Society, 2019)
We present a case of perivulvar squamous cell carcinoma in an 8-year-old crossbred Simmental cow. A tumoral mass, of considerably large volume localized in the perivulvar region and growing at a slow pace, was detected in the animal. The mass, subsequently identified histopathologically and immunohistochemically as squamous cell carcinoma, was surgically excised from the perivulvar region using intrathecal anesthesia.